2019
DOI: 10.15587/2519-4852.2019.178951
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a nanodispersion silica composite with polyhexamethylene guanidine hydrochloride on immunological indicators and indicators of oxidation and antioxidant homeostasis in rats with thermal burn

Abstract: У всьому світі: майже 6 млн осіб щорічно звертаються по медичну допомогу з приводу опікових ран. На сьогоднішній день основним методом місцевого лікування ран та опіків, в тому числі інфікованих, є використання лікарських засобів, що містять антисептики, антибіотики, сорбенти, а також їх сполучення. Мета. Визначити вплив композиту нанодисперсного кремнезему з полігексаметиленгуанидіну гідрохлоридом на імунологічні показники та показники окислювально-антиоксидантного гомеостазу у крові та осередку ураження щурі… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…It was found that the polymeric biocide activates the growth of antioxidants and leukocytes in the blood of animals, which indicates a pronounced reparative ef-fect. In another study, the effect of PHMG-Cl on the immunological and redox homeostasis indices in blood and skin of rats with non-infected thermal burn, has been studied (Doroshenko A et al 2019). PHMG-Cl was found to have pronounced anti-infl ammatory properties and affected redox homeostasis, which is expressed in normalization of the content of markers of free radical oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the polymeric biocide activates the growth of antioxidants and leukocytes in the blood of animals, which indicates a pronounced reparative ef-fect. In another study, the effect of PHMG-Cl on the immunological and redox homeostasis indices in blood and skin of rats with non-infected thermal burn, has been studied (Doroshenko A et al 2019). PHMG-Cl was found to have pronounced anti-infl ammatory properties and affected redox homeostasis, which is expressed in normalization of the content of markers of free radical oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Experience with this type of treatment, mainly in post-Soviet countries, has shown the feasibility of its use in the acute period of allergic diseases and to prevent recurrence of the disease. Today, enterosorption is a component of complex therapy for various types of intoxication, including allergic, with a scientifically based and clinically proven efficacy (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125).…”
Section: Clinical Application Of Enterosorbentsmentioning
confidence: 99%
“…With food and drug allergies and atopic dermatitis, using sorbents in complex therapy leads to more rapid regression of skin rashes and subjective sensations, as well as normalization of the gastrointestinal canal function. There is a positive effect in terms of laboratory parameters such as the decreasing number of eosinophils and level of total IgE in blood (28, 32, 119), increasing in cellular and humoral immunity, in particular, the number of T lymphocytes increases, eosinophilia decreases, level of circulating immune complexes decreases, while content of immunoglobulins class M and E stabilizes, itching reduces, and edema phenomena and hives decrease (24,28,33,34,(113)(114)(115)(116)(117)(118)(119)122). It is significant that at the same time, enterosorbents increase sensitivity to hormones, making it possible to reduce the amount of glucocorticosteroid therapy by 50 percent on average and, in some patients, complete withdrawal of hormonal therapy (32).…”
Section: Clinical Application Of Enterosorbentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another polymeric biocide, PHMG-Cl has broad range of antimicrobial activity, being however much cheaper than PHMB-Cl due to simple one-step synthesis [41]. Recent studies have also shown that PHMG-Cl possesses pronounced anti-inflammatory and wound healing properties and therefore may be used for the treatment of chronic wounds and thermal burns [43]. Thus, PHMG-Cl based composite effectively reduced the level of proinflammatory and increased the level of pro-inflammatory cytokines, as well as normalized the oxidative-antioxidant homeostasis by normalizing the content of markers of free radical oxidation to accelerate the treatment of thermal burns.…”
Section: Introductionmentioning
confidence: 99%